Design and Development of KPRI RSCM Employee Presence Attendance Application Using Android-Based QR Code - Rifky, Muhamad; Faizah, NM; Koryanto, Lucky (Journal Mobile Technologies (JMS), 2023)
RSCM KPRI Services Cooperative is a cooperative that operates in 2 initial tasks, namely providing loans to members with light services and carrying out the distribution of basic goods from the government to members of each company or agency. make attendance. attendance attendance is part of the most important role in every body of work. Where attendance is one of the main supports that can motivate and support all work activities to be carried out in it, using the finger print system in attendance at the Cooperative office which is in the Dr. Cipto Mangunkusumo National General Hospital (RSCM) environment is very at risk of being exposed to various kinds of virus, and one of them is the Corona Virus which is still a pandemic, so that the KPRI RSCM Service Cooperative innovates in the employee attendance system by using a presence system using an Android-based QR Code, so that cooperative employees can take attendance using their personal cell phones. explains how to use the designed application system, namely the KPRI RSCM Employee Presence Application. It is hoped that this application can make it easier for employees to make attendance, and the Personnel section can more easily monitor the attendance of their employees utilizing the Android system as a tool or attendance system that makes it easier for companies and employees, especially at the KPRI RSCM Service Cooperative so that it reduces contact that can cause risk of exposure to the coronavirus.